EROS DALAM KUMPULAN PUISI GAMBAR KESUNYIAN DI JENDELA KARYA SHINTA FEBRIANY - Dahori, Agus; Julian, Royyan (Jurnal Komposisi, 2022)
Examines the problem of eros in the poems Gambar Silence in the Window by Shinta Febriany. The problem expressed in the poem refers to sexual relations which involve elements of male and female intercourse. In order to reveal sexuality in the poem, it is necessary to analyze the expressions that describe body contact so that the correlation of eros in the poem can be interpreted. The purpose of this study is to reveal the beauty of the union of sexuality in the poems Gambar Silence in the Window by Shinta Febriany. In particular, the theory used in this study uses Plato's eros theory to interpret the poems Gambar Silence in the Window by Shinta Febriany. The context in the poem illustrates how a person has intercourse by satisfying the desires that are in the human body to unite. The approach used to understand the poem is literary psychology because eros is included in psychology which is included in the part of human emotion. The steps of this research are: First, read the collection of poems. Second, understanding the issues in a collection of poems. Third, interpreting the results of the reading that has been done and describing poetry with a sexual background. Material objects in the poetry collection Gambar Silence at the Window are limited only to poetry with a sexual background, including "Embrace Wounds", "Replaying Memories", "We Imagine Us", "I Am Not the Future", "Knife Blades for Us". The results of the discussion include the following. First, the common thread in the poem is a relationship that always involves a passionate meeting of the human anatomy. Second, sexuality becomes a way to unite by pouring all the tension of the body. Third, Unification produces a sense of comfort, enjoyment, peace of mind and produces offspring.